The dynamics of the main epidemiological indicators among living in Moscow patients with diabetes mellitus (2013–2018) - Mikhail B. Antsiferov; Nikolay A. Demidov; Marina F. Kalashnikova; Olga V. Duhareva; Olga K. Vikulova; Marina V. Shestakova (Сахарный диабет)
BACKGROUND: State Register of Diabetes Mellitus (SRDM) plays an important role in the dynamic analysis of the epidemiological parameters that evaluate the disease itself and its complications, and also helps to analyze the quality of specialized medical care for patients. To solve modern scientific and practical problems, it is important to analyze data not only among the entire population of Russia, but also in large administrative-territorial subjects of the country. AIMS: To Study the dynamics of the main epidemiological indicators (values) among patients with type 1 diabetes mellitus (DM1) and type 2 diabetes mellitus (DM2) living in Moscow for the period from 2013 to 2018 according to the State Register of Diabetes Mellitus (SRDM). MATERIALS AND METHODS: The analysis of Moscow region of the SRDM database was conducted. According to it there were registered 345.1 thousand patients with diabetes by 01.01.2019. RESULTS: During the period from 2013 to 2018 the total number of patients with DM increased up 9.8% (from 314.4 thousand to 345.1 thousand people). DM2 accounts for 94% of the total number of patients. According to SRDM the prevalence of DM1 on 100 thousand population has grown up 6.9% (from 152.2 in 2013 to 162.7 in 2018); DM2 – by 9.6% (from 2864.7 in 2013 to 3139.4 in 2018). The incidence of DM1 per 100 thousand people decreased down to 6.4% (from 4.7 in 2013 to 4.4% in 2018); DM2 – grew up 4.3% (from 198.1 in 2002, to 206.6 in 2018). Throughout the study period the incidence of DM2 was higher among women, while the opposite trend was observed among women with DM1. The mortality among people with DM1 in 2018 was 1.6 per 100 thousand among adult population (in 2017 it was 1.7); among patients with DM2 the mortality was 56.6 people per 100 thousand among adult population (in 2017 it was 65.6). The first place among the direct causes of death among patients with DM1 and DM2 in 2018 was occupied by cardiovascular diseases (57.5% and 67.9%, respectively), the second place – oncological diseases (9.9% and 12.2%). CONCLUSIONS: The results of the epidemiological analysis showed that since 2013 in Moscow there has been an increase in the prevalence of diabetes, against the background of stable indicators of incidence (except for the organizational period of adapting to the new online data entry system of SRDM). The leading causes of death of patients with diabetes are cardiovascular and oncological diseases.